Clinical researchPrevalence of Behçet’s syndrome in patients presenting with venous thrombosis: prospective study in a cardiovascular outpatient clinic - Erer, Dilek; Gogus, Feride; Tumer, Naim B.; Gunendi, Zafer; Iriz, Erkan; Imren, Veli Y.; Oktar, Gursel L. (Archives of Medical Science, 2009)
Introduction: Behçet’s syndrome (BS) is a vasculitis characterized with oral and genital ulcers and uveitis. Vascular involvement is a serious cause for mortality and morbidity including both arteries and veins of all sizes. The aim of this study was to determine, the prevalence of BS among patients presenting with deep vein thrombosis (DVT) in routine cardiovascular surgery outpatient clinic. Material and methods: One hundred and sixteen patients presenting with signs and symptoms of DVT in our cardiovascular surgery outpatient unit were reviewed between 2005 and 2007. All the patients were searched for the symptoms of BS: history or presence of oral aphthae, genital ulcers, uveitis, erythema nodosa, arthritis or arthralgia, and thrombophlebitis. Routine laboratory blood tests as well as specific thrombotic markers were checked. Pathergy skin test was performed and evaluated at 48 h in suspected individuals. Results: Nine patients were diagnosed with BS. The prevalence of BS among patients presenting with a clinic of DVT in our cardiovascular outpatient unit was 7.5%. Only one of the patients with BS was female. The mean age of the patients was 38.9 years (range: 29-62 years). The patients with BS were significantly younger than the non-BS patients (p < 0.05). Interestingly, only one patient with DVT was previously diagnosed as BS. Conclusions: It is important to keep in mind the differentital diagnosis of Behçet’s syndrome in a cardiovascular outpatient clinic.